2003
DOI: 10.1021/jp0345710
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Electron Spectra of Carbon Allotropes (Diamond, Graphite, Fullerene) by Density Functional Theory Calculations Using the Model Molecules

Abstract: X-ray photoelectron, emission, and Auger electron spectra of diamond, graphite, and fullerene have been analyzed by deMon density-functional theory (DFT) calculations using the model molecules adamantane derivative (C 10 H 12 (CH 3 ) 4 ), pyrene (C 16 H 10 ), and C 60 , respectively. The theoretical valence photoelectron, C KR X-ray emission, and Auger electron spectra for the allotropes are in good accordance with the experimental ones. The combination analysis of the valence X-ray photoelectron and C KR X em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…Differences in this energy range have been modeled for fullerene and graphite [56]. Similarly, Table 6 shows the atomic composition of the glass-epoxy fracture surfaces with the plasma and APS treatments.…”
Section: Figure 6: (A) Experimental and (B) Calculated Vb Spectra Formentioning
confidence: 99%
“…Differences in this energy range have been modeled for fullerene and graphite [56]. Similarly, Table 6 shows the atomic composition of the glass-epoxy fracture surfaces with the plasma and APS treatments.…”
Section: Figure 6: (A) Experimental and (B) Calculated Vb Spectra Formentioning
confidence: 99%
“…We observe some change in the intensity and positon, not clearly related to the stress. Finally, in relation to the deeper s-type states, there is a peak at 246.4 eV, which is not significantly altered with stress and has the same intensity at the same energy in each of the samples and may be a characteristic peak of amorphous carbon, given by a miscellany between states formed by graphite and diamond bonds [15] In summary, it is observed that, in the KVV spectrum range, using the second derivative method, the most external electronic states (above 264.1 eV, i.e., and states) are more influenced by stress than the sp hybrid states.…”
Section: Resultsmentioning
confidence: 91%
“…This correspondence between DOS and carbon KVV spectra was observed and studied by Lascovich and coauthors [10], where the validity of the weak interaction between holes is the energy region next to the Fermi level ( band). On the other hand, some theoretical efforts have also been made in understanding the experimental Auger spectra, starting from known principles of electronic states [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…At ~13 eV the 2s σ(C-C) electron states are identified as an especially distinct feature ≥900 °C instead of merging with the subsequent C 2s signal, followed by the main C 2s peak at ~18 eV. 57,59,60 A prominent signal in the O 2s region associated with oxygen bound to the aromatic carbon lattice (σ(C-O)) disappears after deoxygenation. 40,59,61 Interestingly, this feature reappears on GF-980 with a lower separation to the C 2s peak because of phenyl instead of primarily C-O-C or C=O groups being present.…”
Section: Influence Of the Deoxygenation On The Electronic Structurementioning
confidence: 99%